Synthesis and glycosidase inhibition potency of all-trans substituted 1-C-perfluoroalkyl iminosugars. (15th July 2018) - Massicot, Fabien; Plantier-Royon, Richard; Vasse, Jean-Luc; Behr, Jean-Bernard
Abstract: Synthetic analogues of the naturally occurring iminosugar homoDMDP, which feature a perfluoroalkyl group at the pseudo-anomeric position, have been synthesized from the corresponding sugar-derived cyclic aldonitrone. The new fluorinated iminosugars as well as homoDMDP and its 6-deoxy counterpart were evaluated for their inhibitory activity against a panel of glycosidases. While the replacement of the (1′, 2′)-dihydroxyethyl substituent of homoDMDP with –C4 F9 proved detrimental for enzyme binding, introduction of a –C3 F7 moiety tuned the inhibitory activity spectrum selectively towards α-fucosidase and α-glucosidase from yeast. Graphical abstract: Highlights: Synthesis of perfluoroalkyl iminosugars with an all- trans stereochemistry (homoDMDP series). In situ generation of a perfluoroalkyl Grignard reagent, which adds to chiral nitrone with complete stereoselectivity. Heteronuclear OESY NMR experiments to assign configuration. Evaluation of yeast α-glucosidase activity in function of pH to fix the test conditions compatible with protonation of amine. Evaluation of the perfluoroalkyl iminosugars and control compounds (homoDMDP and 6-deoxy-homoDMDP) towards glycosidases.